(untitled) (Bioagro, 2026)
Globally, salinity stress ranks as one of the most detrimental abiotic stresses constraining agricultural performance. This study evaluated the efficacy of foliar-used ascorbic acid (AsA) and proline (Pro), used separately or concurrently, in mitigating the deleterious effects of saline irrigation (2000 and 4000 mg·L-1) on the growth and productivity of tomato (cv. Super Strain). Salinity stress significantly reduced plant height, leaf area, dry biomass as well as and yield components. It also led to marked declines in chlorophyll pigments (chl. a, b, and total chl.) and relative water content. In contrast, salinity stress induced increases in endogenous proline and total phenolic contents in leaves. Foliar use of AsA and Pro, whether used independently or in combination, successfully reduced the harmful consequences of salt stress, leading to notable improvements in growth traits, chlorophyll concentration, leaf water status, and fruit yield. Furthermore, treatments enhanced the activities of catalase, peroxidase, and superoxide dismutase and stimulated the endogenous production of proline and phenolic contents. The combined application of AsA and Pro consistently produced the most pronounced improvements across all measured parameters. These findings suggest that the integrated use of AsA and Pro as foliar sprays represents a potential strategy to improve salinity tolerance and sustain tomato productivity under saline conditions.